“CHOLIL NAFIS' THOUGHTS ON THE URGENCY OF PREACHER CERTIFICATION” - Wanda Triyanti; Diya Ayu Luspita W; Haris Akhad M; M Fikri Fahrezi; Livana Azzahro; M. Naufal Aziz; Aji Pangestu (PT. Intelek Cendikiawan Nusantara, 2025)
The development of da'wah in the digital era presents new complex challenges, including issues of scientific authority, communication ethics, and the dominance of popularity over substance. This study aims to examine KH Cholil Nafis's thoughts on the urgency of preacher certification as a strategy to improve the quality of professional and ethical da'wah. With a qualitative approach, data is obtained through content analysis of digital lectures, literature studies, and in-depth interviews. The stages of analysis are carried out through a data reduction process to filter relevant information, verify findings with da'wah communication theory, and draw conclusions based on thematic patterns. The results show that certification is not merely administrative, but an important mechanism in ensuring that preachers have an understanding of Wasathiyah Islam, digital literacy, and social sensitivity. Certification also opens up space for ethical control that was previously minimal in the digital da'wah ecosystem. The findings confirm the importance of a multidisciplinary approach in contemporary da'wah studies, combining da'wah communication, branding strategies, and digital ethics. This research enriches the digital da'wah literature while providing practical recommendations for religious institutions to formulate professional, inclusive, and contextual da'wah policies.